O Fundo da ONU para a democracia (UNDEF): promoção da democracia e prioridades estratégicas para as organizações da sociedade civil no Brasil - Souza, Caroline Matias de (2023)
The UN Fund for Democracy is the first United Nations body to specifically address issues relating to financing democracy in the world and has a unique role in financing projects carried out by civil society organizations. Taking this into account, the present work asked itself: what has been the role of UNDEF/UN in preventing democratic disruption in Brazil? And what type of democracy does UNDEF finance? The hypothesis raised was that the Fund has been financing organizations and projects that are aligned with the notion of hegemonic liberal democracy since the 1990s. To verify this hypothesis, we researched UNDEF's performance between the years of its creation to the present day and We profile (i) the organizations that are supported by the Fund in Brazil and (ii) the types of projects that are supported by it. Among the main reasons that justify this choice is the fact that Brazilian CSOs have historically entered into partnerships with the Brazilian government in all its spheres to be able to put into practice their projects of public interest, but the diversification of financiers becomes a central part of the sustainability strategies of CSOs. Strategically, the research was limited to the Fund's financing of projects carried out in Brazil. Among the results obtained we list: (i) UNDEF has financed organizations that already have some degree of exposure on the domestic and international public scene; (ii) small organizations such as neighborhood organizations and social movements are not among the institutions financed by the Fund; (iii) the assistance and promotion of democracy carried out by the UN is close to the vision of hegemonic liberal procedural democracy. The interest in this topic came from a professional interest, as she is a project analyst within an organization that carries out several partnerships with the public sector and constantly competes for international and national notices to ensure the execution of public interest activities, public and private. We hope that the conclusions of this work will be useful for Brazilian organizations that are interested in understanding more about UNDEF's activities in Brazil